21st Century Learning to Produce Vocational Graduates in the Industrial Age Competitively 4.0 - Syaiful Efendi, Bella Cornelia Tjiptady, Rico Andhika Putra (International Conference on Industrial Revolution for Polytechnic Education, 2019)
The fourth industrial revolution (industry 4.0), among others, marked the emergence of the internet (cyber), supercomputers, smart robots, micro chips, editing genetic, and neurotechnology that allows humans to further optimize brain function. Where one form of implementation is the use of robots to replace human beings so that it is cheaper, more effective and efficient. The implication, will change the pattern of life and human interaction, because fundamentally there have been technological changes with new approaches that combine the physical, digital, and biological worlds. Industry 4.0 requires workers who have skills in digital literacy, technology literacy, and human literacy. So that vocational education should be able to innovate and be creative in responding to the challenges and opportunities of the implications for the industry 4.0 with the revitalizing system vocational education that includes learning systems, educational units, students, teachers, and education staff.